Favorable interleukin-8 induction in human gingival epithelial cells by the antimicrobial peptide LL-37 - Montreekachon,P. (The Allergy and Immunology Society of Thailand, 2015)
© 2014, Allergy and Immunology Society of Thailand. All rights reserved. Results: Out of eleven Th1/Th2 cytokines tested, treatment of HGECs with non-toxic doses of LL-37 (2-6 μM) significantly raised only IL-8 levels in the cell-free culture supernatants, when compared to control untreated cells (P <0.05). Consistent with the elevated IL-8 levels, IL-8mRNA expression was remarkably and significantly induced by LL-37 treatment (P <0.05), when compared to the modest mRNA induction of other three cytokines, including IL-1β, IL-6, and TNF-α. The time-course study demonstrated a cumulative IL-8 mRNA induction by LL-37 treatment within a 24-hour interval. Conclusions: These findings indicate that LL-37 favorably induces IL-8 expression and secretion in HGECs, suggesting both direct and indirect involvement of LL-37 in neutrophil recruitment into an inflammatory site within diseased periodontal tissues. Background: LL-37, the only member of the antimicrobial peptide cathelicidin family in humans, exerts a variety of biological activities, especially immunomodulation through either direct chemotactic activity or up-regulation of several cytokines and chemokines in various cell types. In this study, we aimed to determine the immunoregulatory effect of LL-37 on Th1/Th2 cytokine expression and production in human gingival epithelial cells (HGECs). Methods: Cultured HGECs were treated with different concentrations of LL-37 for different numbers of times. The cytotoxicity of LL-37 was determined by an MTT assay. Total RNA was isolated for RT-PCR and real-time PCR analyses of cytokine expression. Cell-free culture supernatants were assayed for Th1/Th2 cytokine levels by a cytokine bead array.